Torque Ripple Analysis for IPM AC Motors. Issue 5 (19th August 2014) - Shen, Jianxin; Shi, Dan; Wang, Canfei; Li, Peng; Wang, Kang; Jin, Mengjia; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper is to investigate a new cause of torque ripple in interior permanent magnet (IPM) alternating current (AC) motors, which is common but has hardly been studied. The paper also proposes a new method to suppress the total torque ripple. Design/methodology/approach Besides the well-known cogging torque and mutual torque ripple, a new ripple which exists in the reluctance torque is found. It is verified with both analytical model and finite element analysis (FEA). Also, a novel method is proposed to reduce the reluctance torque ripple, with experimental validation. Findings It is usually said that the winding inductances of an IPM AC motor vary sinusoidally with the rotor position, thus, the d-axis and q-axis inductances are constant, whilst the reluctance torque is smooth. However, in most practical motors, the inductances vary irregularly, causing a significant ripple in the reluctance torque. Moreover, in machine design, it is always desirable to suppress the cogging torque as much as possible. However, in this paper, it is proved that the cogging torque can remain and be used to cancel the reluctance torque ripple. Originality/value Torque ripple in the IPM AC motors is usually reduced by suppressing the cogging torque and making both back electromotive forces (EMFs) and currents sinusoidal. However, this paper reveals the new cause of the torque ripple due to the irregular variation of winding inductances. Moreover, the paper gives a new method to cancel the reluctance torque ripple with the cogging torque.